Morphological and biochemical profile of ex situ conserved Homalomena aromatica (Schott) - an underutilised indigenous tuber crop - P. Murugesan; Dinesh Prasad Semwal; Soyimchiten Longkumer; A.N. Jyothi; P.S. Shameer; Manju Baby; Akhila Anil (JOURNAL OF ROOT CROPS, 2025)
Abstract Two germplasm accessions (CTCRI-PM-HA-01 and CTCRI-PM-HA-02) of rhizomatous herb Homalomena aromatica collected from Cachar, Assam were evaluated under ex situ conditions (ICAR- CTCRI, Thiruvananthapuram) for 17 quantitative and 28 qualitative characters along with biochemical profile including essential oil for improvement and conservation. Under the quantitative characterisation, the highest standard deviation was observed for tuber weight (18.4) followed by tuber length (16.5) and plant span (9.19). Standard deviation was highest for moisture content (10.4) followed by total starch (4.77) and crude protein (1.14) when considering mean nutrient values of stem, leaf and rhizome. The germplasm accessions exhibited similarity for 57.14% and differed for 42.85% in qualitative characters. The discriminated qualitative traits are leaf base shape (with regard to the petiole attachment), predominant position (shape) of leaf lamina surface, leaf blade margin, leaf blade colour variegation, type of variegation, leaf blade margin colour, petiole junction colour, petiole stripe, rhizome shape, rhizome cortex colour, rhizome flesh colour of central part and root colour. The average estimated values observed for important nutrients viz., total starch, fibre, fat and crude protein are 11.4, 2.53,1.48, 2.75 in rhizome 3.3, 1.73, 2.43,0.47 in stem, 2.97, 2.75, 2.63 and 1.55 in leaves, respectively. Rhizome contains 0.235% essential oil. Outcome of this research is that H. aromatica exhibited variations for economically important traits and accordingly, trait specific germplasm exploration and conservation are to be undertaken.